Interferometric methods for spatio temporal seismic monitoring in underground mines. Issue 2 (31st May 2017) - Dales, Philippe; Audet, Pascal; Olivier, Gerrit; Mercier, Jean-Philippe
Abstract: In active underground mining environments, monitoring of the rockmass has important implications for both safety and productivity. Monitoring can be accomplished by exploiting the many passive seismic sources (microearthquakes, drilling, ore-crushers etc.) around the mine on the condition they can be accurately detected and located. We implement a popular beamforming-like approach that uses cross-correlation functions in a maximum likelihood search to locate sources of seismic energy. We illustrate the technique with a synthetic example in which two simultaneous sources are located and discuss briefly the effects of different processing parameters. We demonstrate the effectiveness of this technique by monitoring both impulsive sources (microearthquakes) and other persistent sources (drilling and ore-crushers) in two active underground mines. We then propose how this information can be used in conjunction with ambient seismic noise interferometry to estimate seismic Green's functions under temporally variable and anisotropic wavefield conditions. Alternatively, we demonstrate how stable persistent sources, typically seen as contaminants in ambient noise applications, can be used to monitor changing rockmass conditions and potentially guide mining operations.